Indian registration act - Sirohi, J. P. S.; Sirohi, Sunil (Faridabad Allahabad Law Agency, 2021)
The study of the Registration Act also includes satisfying the relevant provisions of other relevant acts as submitted above, among others. The Bench, Bar, litigants, intellectuals and others cannot underestimate the legal impact of the provisions of the Registration Act and other concerned Acts. A lawyer need to be properly conversant with these concepts and provisions to advance in the legal profession. Even the judiciary, from the Apex Court to the courts below, sometimes face complicated legal issues for non-registration of immovable properties, cancellation of the registered sale deeds and non-payment of other duties and fees provided in different Acts as the documents can only be exhibited during the evidence when there is a compliance of these provisions. Interpretation of the provisions of the Registration Act and other related provisions of other Acts is also crucial and there are number of cases decided by the lower judiciary being challenged in the higher courts including the Apex Court for their decisions on these complicated legal matters. Sometimes there are conflicting decisions of the Supreme Court bench while deciding cases under this Act.
Keywords: Registration act